Bioequivalency Study of Two Formulations of Ketoconazole Tablet in Healthy Volunteers: Bioequivalenecy of ketoconazole tablets - Sadeghnia, Hamid R.; Hassanzadeh-Khayyat, Mohammad (Iranian Journal of Pharmaceutical Sciences, 2005)
In this study, the pharmacokinetic parameters of two marketed tablet formulations of ketoconazole were studied, and the relative bioavailability of the test formulation was compared with a reference formulation. A single dose (12x2) double blind randomized cross-over study of a generic formulation of ketoconazole tablet (2x200 mg), and a commercial brand, Nizoral tablet (2x200 mg, Janssen Pharmaceutica Beerse Belgica) was carried out. All of the tablets met the United States Pharmacopoeia dissolution specifications. The plasma level of ketoconazole was determined by using a modified rapid and selective reverse phase HPLC method. Plasma data was used to evaluate the relative bioavailability and other pharmacokinetic parameters characterizing rate [peak plasma concentration (Cmax) and time of peak concentration (Tmax)] and the extent of absorption (AUC). The mean peak plasma concentration (Cmax) of ketoconazole of the two different formulations, A (reference) and B (test), were 7.08±2.81 and 6.74±2.20 mg/l at 1.70±0.48 h and 1.73±0.75 h, respectively. The mean AUC0− ∞ of the two products, were 39.07±16.25 and 31.85±14.64 for Aand B, respectively. Statistical analysis showed no significant d i fferences between various pharmacokinetic parameters of the two different formulations. The 90% parametric confidence intervals for the mean of test/reference ratios of Cmax, AUC0- 12,AUC0−∞ and Cmax/AUC0−∞ were within the bioequivalence acceptable range (80-125%). Results of this study showed that the extent and rate of absorption of ketoconazole tablets tested are comparable and the generic formulation is bioequivalent to the commercial product.